The relative importance of financial and non-financial analysis in project evaluation – evidence from portuguese firms - Moutinho, Nuno (2014)
Project appraisal has traditionally put its emphasis on the financial aspects of projects, mainly the quantitative ones, underestimating other areas of analyses where factors of a qualitative nature, intangible and subjective, may also affect the implementation and value of projects. Non financial evaluation supply information about less tangible factors and is expected to identify competitive advantages and risks that financial techniques cannot capture. In general there are few empirical studies addressing these other aspects. Most surveys are addressed to the financial techniques. We have done a survey, aimed at the non financial aspects of projects, which is the base of two papers. In this first paper, we aimed to identify the importance of non financial aspects at the decision making process and the evaluation of projects, and in particular to investigate the practices of Portuguese companies in this field. The results of our study support the importance of incorporating non financial aspects into the appraisal of projects, and show how some of those aspects have greater relevance than that attributed to the financial elements. The study also points to the strategic and technical aspects of projects as the most relevant non financial factors considered by Portuguese firms. The financial analysis, according to the empirical data collected, comes only in third place of importance, both at the appraisal and at the decision-making stages. Commercial factors, showed similar relevance to the financial ones.